Downregulation of miR-1826 Indicates a Poor Prognosis for Osteosarcoma Patients and Regulates Tumor Cell Proliferation, Migration, and Invasion - Peng Li; Lei Wei; Wenshuai Zhu (International Journal of Genomics)
Background. Osteosarcoma (OS) is the most frequent bone tumor with high metastasis. This study is aimed at assessing the expression and prognostic significance of microRNA-1826 (miR-1826) in OS patients, as well as its biological function in tumor progression. Methods. Quantitative Real-Time PCR was employed to measure the expression of miR-1826 in OS tissues and cell lines. Kaplan-Meier survival analysis and Cox regression model were used to evaluate the prognostic value of miR-1826. CCK-8 and Transwell assay were conducted to investigate the effect of miR-1826 on OS cell proliferation, migration, and invasion. Results. miR-1826 expression was downregulated in OS tissues and cell lines and associated with OS patients’ clinical stage and distant metastasis. Low levels of miR-1826 were related with shorter survival time and determined as an independent prognostic indicator for the overall survival of OS patients. The overexpression of miR-1826 in OS cells led to inhibited cell proliferation, migration, and invasion. Conclusion. The decreased expression of miR-1826 predicts a poor prognosis in OS patients, and its overexpression inhibits OS cell proliferation, migration, and invasion. This newly identified miR-1826 provides a novel sight into the pathogenesis of OS and offers a candidate prognostic biomarker and therapeutic target for OS treatment.